2017
DOI: 10.1016/j.ecoleng.2017.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Experimental optimisation of various cultural conditions on urease activity for isolated Sporosarcina pasteurii strains and evaluation of their biocement potentials

Abstract: Microbially induced carbonate precipitation (MICP) is a process that has emerged as an attractive alternative ground improvement technique in Geotechnical and Civil Engineering using ureolytic bacteria for soil strengthening and stabilisation. Locally isolated Sporosarcina pasteurii from limestone cave samples of Sarawak were found to have high urease-producing abilities. Optimisation of various cultural conditions (incubation temperature, initial pH medium, incubation period and urea concentration) were perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
68
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 173 publications
(69 citation statements)
references
References 48 publications
1
68
0
Order By: Relevance
“…Lysinibacillus xylanilyticus reported in this paper showed the highest activity at weak alkali conditions. Similar phenomena could be seen on certain microbial urease like Sporosarcina pasteurii [23,40], Pararhodobacter sp. [27] and Klebsiella aerogenes [44], those have the optimum activity under weak alkaline conditions.…”
Section: Discussionsupporting
confidence: 73%
See 3 more Smart Citations
“…Lysinibacillus xylanilyticus reported in this paper showed the highest activity at weak alkali conditions. Similar phenomena could be seen on certain microbial urease like Sporosarcina pasteurii [23,40], Pararhodobacter sp. [27] and Klebsiella aerogenes [44], those have the optimum activity under weak alkaline conditions.…”
Section: Discussionsupporting
confidence: 73%
“…Numerous investigators have studied the effect of temperature on the rate of urea hydrolysis of many soil bacteria [23,27,30,40]. In general, their results have indicated that the rate of urea hydrolysis increases with increasing temperature, suggesting that the urease of most of the soil bacteria is not heat inactivated (up to the temperature ranging 45-60 °C).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The conductivity values were recorded and used to plot the gradient (mS cm ‐1 min ‐1 ) before being converted to urease activity (mol urea hydrolysed per minute) with regard to the dilution factor (Omoregie et al . ). A calibration curve was previously performed by Whiffin () under standard condition at 25°C with purified urease (Sigma Cat.…”
Section: Methodsmentioning
confidence: 97%